2009
DOI: 10.26719/2009.15.3.600
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of cancer in Gulf Cooperation Council countries, 1998-2001

Abstract: We describe the patterns of cancer incidence for common cancers in Gulf Cooperation Council countries during 1998-2001. A total of 32 291 cases of cancer were diagnosed (16 342 in males; 15 949 in females). Male preponderance was observed only in Saudi Arabia and Oman. The age-standardized incidence of all malignancies per 100 000 in both sexes was highest in Qatar followed by Bahrain, Kuwait, Oman, UAE and Saudi Arabia. Paediatric cancer ranged from 9.5% of total cancers in Saudi Arabia and UAE to 4.0% in Bah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 5 publications
0
44
0
Order By: Relevance
“…This explains the current low prevalence of smoking, lung cancer and COPD amongst older Emiratis [18], [19]. However after the discovery of oil, the UAE experienced very rapid growth that resulted in massive migration of an expatriate workforce.…”
Section: Discussionmentioning
confidence: 99%
“…This explains the current low prevalence of smoking, lung cancer and COPD amongst older Emiratis [18], [19]. However after the discovery of oil, the UAE experienced very rapid growth that resulted in massive migration of an expatriate workforce.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is common in the Middle East. A study of cancers in the Gulf countries found that lung cancer ranked first among all malignancies among men and second among Bahraini women 122 . The incidence is steadily rising among men and women; cigarette smoking is the main risk factor for this condition 123 .…”
Section: Pulmonary Pathology In the Middle Eastmentioning
confidence: 99%
“…All six GCC countries curate national cancer registries that provide statistics measures to the Gulf centre for cancer registration [ 67 - 70 ]. Remarkably, the national cancer registers of Bahrain, Kuwait, Oman, and Qatar are listed in a high incidence data quality category as assessed by the international agency for research on cancer (IARC) [ 71 ].…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, prostate cancer is less frequent in the Gulf region, especially in Saudi Arabia [ 75 ]. In most common cancer types including thyroid and breast cancer, patients are several years younger at first diagnosis compared to Western countries [ 67 , 72 , 76 , 77 ]. Molecular genetics studies from the Gulf region have demonstrated that hereditary components like single nucleotide polymorphisms (SNPs) confer risk for breast [ 78 ] and thyroid cancer [ 79 , 80 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation